Impact of rigid central clamps on longitudinal deformation of long-span suspension bridges under vehicle excitations. Issue 6 (3rd June 2022) - Gao, Wenbo; Li, Guangling; Su, Quanke; Han, Wanshui
Abstract: The presence of rigid central clamps (RCCs) minimises the damage potential of short suspenders and expansion joints in in-service long-span suspension bridges. The study presented in this paper evaluated the impact of the presence of RCCs on the longitudinal deformation of a long-span suspension bridge under live load with vehicle braking and random traffic flow excitations. Two finite element (FE) models of the bridge were developed – one with RCCs and the other with a traditional suspender (TS) at mid-span. The impact of RCCs and TS on the structural system response was evaluated by comparing the dynamic characteristics of the models. The exceeding probabilities of longitudinal deformation under different traffic flow levels during the design reference period were obtained. The simulation results show that the RCCs are capable of reducing the longitudinal deformation by 35% to 45%. The unfavourable exceeding probabilities of longitudinal deformation over the design threshold decreased from 1.0 to 0.0002, showing that the RCCs could be an effective measure to enhance the service life of the shortest suspender and expansion joints of long-span suspension bridges.